2021
DOI: 10.1002/adma.202104308
|View full text |Cite
|
Sign up to set email alerts
|

Direct Chemical Vapor Deposition Synthesis of Porous Single‐Layer Graphene Membranes with High Gas Permeances and Selectivities

Abstract: yield orders of magnitude higher gas permeances because of its atomic thickness and low cross-membrane transport resistance. [3,4] Because perfect single-layer graphene is almost impermeable to gases, [5,6] in-plane pores, which are vacancy defects in the graphene lattice, are necessary for gas permeation. To realize the enormous potential of porous graphene for gas separation, the areal pore density in graphene should be considerably high. Our group theoretically predicted that the pore density needs to excee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 80 publications
1
34
0
Order By: Relevance
“…The oxidatively etched NATMs not only exhibited higher selectivities than The experimental results are categorized according to the perforation methods used, including ion beam bombardment (some followed by additional chemical etching), [150][151][152][153][154]156,157] oxidative etching, [143,[158][159][160][161][162][163][164][165][166] and intrinsic defect formation during CVD. [62,143,149,159,160,164,[167][168][169][170][171] The Robeson upper bounds for polymers are plotted assuming 1 µm thickness. [11] the Knudsen selectivities, but also surpassed the 2008 Robeson upper bound of polymeric membranes for H 2 /CH 4 separation and CO 2 /N 2 separation (assuming 1 µm thickness).…”
Section: Oxidative Etchingmentioning
confidence: 99%
“…The oxidatively etched NATMs not only exhibited higher selectivities than The experimental results are categorized according to the perforation methods used, including ion beam bombardment (some followed by additional chemical etching), [150][151][152][153][154]156,157] oxidative etching, [143,[158][159][160][161][162][163][164][165][166] and intrinsic defect formation during CVD. [62,143,149,159,160,164,[167][168][169][170][171] The Robeson upper bounds for polymers are plotted assuming 1 µm thickness. [11] the Knudsen selectivities, but also surpassed the 2008 Robeson upper bound of polymeric membranes for H 2 /CH 4 separation and CO 2 /N 2 separation (assuming 1 µm thickness).…”
Section: Oxidative Etchingmentioning
confidence: 99%
“…Size and density of these defects are sensitive to the CVD environment (precursor, temperature, pressure, relative concentrations of precursors, etc.) and the catalytic substrate [11, 29, 31, 36, 44, 45] . Currently, there is a lack of characterization technique which can distinguish between the relative population of grain boundary and intragrain defects.…”
Section: Resultsmentioning
confidence: 99%
“…and the catalytic substrate. [11,29,31,36,44,45] Currently, there is a lack of characterization technique which can distinguish between the relative population of grain boundary and intragrain defects. This is mainly because these defects are present in a low density and it is extremely challenging to search them in highresolution mode in HRTEM.…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, Yuan et al. reported the CVD synthesis of nanoporous graphene to produce monolayered graphene membranes demonstrating the highest hydrogen to methane permeation selectivity reported so far ( Yuan et al., 2021 ). The authors observed a larger number of nanopores at a growth temperature of 800°C, as compared to 900°C.…”
Section: Knowledge Gaps and Future Research Directionsmentioning
confidence: 99%